A radar study on the frequency of occurrence of cumulonimbus clouds around Delhi - CHATTERJEE , RN; PRAKASH, PREM (MAUSAM, 1986)
Precise knowledge of the frequency of occurrence of cumulonimbus clouds as well as heights of their- tops is pertinent for safe air navigation. A study has, therefore, been made of the frequency of occurrence of cumulonimbus clouds in the Delhi region based in the data collected with the help of a high power radar, of convective clouds within 100 km around Delhi during the 22-year period, June 1958 to May 1980. The study has indicated that about 46 per cent of the convective clouds depict features of cumulonimbus development. Among these, in about 90 per cent cases, cloud tops have been limited to 12 km. In only 1.6 per cent cases, tops have penetrated the tropopause. The maximum cloud top height observed has been 20 km. Details of the study are presented.